Analysis of students perceptions of democracy quality and civic behavior among uny students"™ - Sutrisno, Cucu; Suyato, Suyato; Mulyono, Budi; Nurhayati, Iffah (Jurnal Pendidikan PKN (Pancasila dan Kewarganegaraan), 2025)
This study aims to analyze the relationship between students' perceptions of the quality of democracy in Indonesia and their civic behavior. Using a quantitative descriptive survey method, this research involved 737 respondents who were students at the State University of Yogyakarta (UNY), selected through random sampling. Data collection took place from May to October 2024 at UNY. Through Spearman's correlation analysis, the study found a correlation coefficient of 0.360 with a significance level of 0.01. This result indicates a positive relationship between students' perceptions of democracy quality in Indonesia and their civic behavior. However, the relationship between the two variables is relatively weak, as the correlation coefficient is far from one. In other words, although students' perceptions of democracy somewhat influence their civic behavior, the impact is not strong enough. These findings suggest the need for additional efforts to improve the quality of democracy in Indonesia to foster more active and positive citizenship among students. This study emphasizes that citizenship education in higher education institutions to strengthen students' understanding of democracy and enhance their participation as democratic citizens